The Effect of Using Constructivist Teaching Approach Model on the Achievement, Creation of an Integrated Conceptual Structure and Attitudes of Al-Hussein Bin Talal University Students Towards Islamic Culture. - Omer Salim AlKhteeb; Talal Abdullah Al-Zoabi (Sultan Qaboos University, 2009)
This study aimed at investigating the effect of A Constructional Learning Model on the achievement, creation of an Integrated Conceptual Structure and attitudes of Al-Hussein Bin Talal University students towards Islamic culture. The sample of the study consisted of 120 students at Al-Hussein Bin Talal University. The sample was divided into two groups: control and an experimental. Three tools were used in conducting this study: a) Test of Islamic culture concepts, b) Test of conceptual integration, c) and Scale of Students' attitudes towards Islamic culture course.The findings of the study were: There was a statistically significant difference between the mean cores of the experimental and control group in the test of the Islamic culture concepts in favor of the experimental group. There was a statistically significant difference between the mean scores of the experimental and control group in the test of conceptual integration in favor of the experimental group. There was a statistically significant difference between the mean scores of the experimental and control group in the students' attitudes towards the Islamic literacy in favor of the experimental group, researchers recommend the use of the constructivist learning model in teaching Islamic culture for other university students. They also recommend developing learning materials based on this model and train instructors of Islamic culture/ to use them.